Sun Protection Knowledge and Behaviors Among Agricultural Industry Workers in Pennsylvania - Camille Moeckel; Robert Bower; Calista Long; Hannah Flamini; Amy Longenecker; Elizabeth M. Billingsley; Eugene J. Lengerich; Charlene Lam (Journal of Agromedicine, 2025)

Coral reef thermal microclimates mapped from the International Space Station - J. Longenecker; F. Benzoni; N. Dunn; H. E. Fox; A. Gleason; D. Otis; V. Chirayath; N. Oury; S. J. Purkis (Coral Reefs, 2025)
Satellite sea surface temperature (SST) is critical for describing marine environments. Traditional SST data, such as those provided by the Group for High Resolution Sea Surface Temperature (GHRSST) program, are valuable, but have a relatively coarse spatial resolution for mapping coral reef thermal environments. Hence, fine resolution SST from orbit would be of great utility to the coral reef research community and speed the pathway to an increased understanding of how, when, and where thermal stress afflicts individual reefs. Such data would support adaptive management, especially so for the design of marine protected areas. Flying aboard the International Space Station, the NASA ECOsystem Spaceborne Thermal Radiometer Experiment on Space Station (ECOSTRESS) instrument may already fill this niche with a spatial resolution 204 times finer than GHRSST. To evaluate ECOSTRESS thermal data over reef environments, we deployed 21 temperature loggers over three years across two reef sites in the Red Sea. We compared temperature retrievals from both the coarse resolution GHRSST and the fine resolution, experimental, ECOSTRESS, to this in-situ logger dataset. While temperature data from both orbital platforms correlated strongly with the logger recordings, only ECOSTRESS, with its 70-m pixels, could construct thermal microclimate maps capturing the dynamic temperature fluctuations experienced by our studied reefs. We contend that ECOSTRESS represents a significant advancement in the capability to monitor heat stress on reefs from orbit.

Mercury exposure of tidal marsh songbirds in the northeastern United States and its association with nest survival - Katharine J. Ruskin; Garth Herring; Collin A. Eagles-Smith; Alyssa B. Eiklor; Chris S. Elphick; Matthew A. Etterson; Christopher R. Field; Rebecca A. Longenecker; Adrienne I. Kovach; W. Gregory Shriver; Jennifer Walsh; Brian J. Olsen (Ecotoxicology, 2022)

Short-Term Resilience of New Jersey Tidal Marshes to Hurricane Sandy - Rebecca A. Longenecker; Jacob L. Bowman; Brian J. Olsen; Samuel G. Roberts; Chris S. Elphick; Paul M. Castelli; W. Gregory Shriver (Wetlands, 2018)

Archaeological Evidence of Validity of Fish Populations on Unexploited Reefs as Proxy Targets for Modern Populations - KEN LONGENECKER; YVONNE L. CHAN; ROBERT J. TOONEN; DAVID B. CARLON; TERRY L. HUNT; ALAN M. FRIEDLANDER; EDWARD E. DEMARTINI (Conservation Biology, 2014)
Reef‐fish management and conservation is hindered by a lack of information on fish populations prior to large‐scale contemporary human impacts. As a result, relatively pristine sites are often used as conservation baselines for populations near sites affected by humans. This space‐for‐time approach can only be validated by sampling assemblages through time. We used archaeological remains to evaluate whether the remote, uninhabited Northwestern Hawaiian Islands (NWHI) might provide a reasonable proxy for a lightly exploited baseline in the Main Hawaiian Islands (MHI). We used molecular and morphological techniques to describe the taxonomic and size composition of the scarine parrotfish catches present in 2 archaeological assemblages from the MHI, compared metrics of these catches with modern estimates of reproductive parameters to evaluate whether catches represented by the archaeological material were consistent with sustainable fishing, and evaluated overlap between size structures represented by the archaeological material and modern survey data from the MHI and the NWHI to assess whether a space‐for‐time substitution is reasonable. The parrotfish catches represented by archaeological remains were consistent with sustainable fishing because they were dominated by large, mature individuals whose average size remained stable from prehistoric (AD approximately 1400–1700) through historic (AD 1700–1960) periods. The ancient catches were unlike populations in the MHI today. Overlap between the size structure of ancient MHI catches and modern survey data from the NWHI or the MHI was an order of magnitude greater for the NWHI comparison, a result that supports the validity of using the NWHI parrotfish data as a proxy for the MHI before accelerated, heavy human impacts in modern times. Evidencia Arqueológica de la Validez de Poblaciones de Peces en Arrecifes Sin Explotar como Objetivos de Apoderamiento para Poblaciones Actuales

MUC1-specific CTLs are non-functional within a pancreatic tumor microenvironment - Pinku Mukherjee; Amelia R. Ginardi; Cathy S. Madsen; Teresa L. Tinder; Fred Jacobs; Joanne Parker; Babita Agrawal; B. Michael Longenecker; Sandra J. Gendler (Glycoconjugate Journal, 2001)

A rat model to study the role of STn antigen in colon cancer - Shunichiro Ogata; Immanuel Ho; Joseph Maklansky; Anli Chen; J. Lawrence Werther; Mark Reddish; B. Michael Longenecker; Elin Sigurdson; Seichiro Iishi; Jie-Yu Zhang; Steven H. Itzkowitz (Glycoconjugate Journal, 2001)